Photoacoustic Imaging for Periodontal Disease Examination - Windra Sari, Atika; Widyaningrum, Rini; Yana, Mitra (Journal of lasers in medical sciences, 2022)
After caries, periodontal tissue inflammation (periodontitis) is the most common oral health problem. Photoacoustic imaging (PAI) is a new technique that uses simple components such as a diode laser and a condenser microphone. This study aimed to evaluate the performance of a simple PAI system in periodontal disease imaging by using an animal model. Normal periodontal and periodontitis tissues were obtained from Sprague-Dawley rats categorized as the control group, treatment group 1 (7 days of periodontitis induction), treatment group 2 (11 days of periodontitis induction), and treatment group 3 (14 days of periodontitis induction). The PAI system was controlled by LabVIEW and Arduino IDE software from a personal computer. Results revealed that the optimal frequency of laser modulation for periodontal tissue imaging was 19 kHz with a duty cycle of 50%. The photoacoustic (PA) intensity of periodontal tissues was -68.71 dB for treatment group 3, -70.34 dB for treatment group 2, -71.69 dB for treatment group 1, and --73.07 dB for the control group. PA image analysis showed that the PA intensity from periodontal disease groups was higher than the control group. This study indicates the feasibility of using a simple PAI system to differentiate normal periodontal tissues from periodontitis tissues.